Syringocystadenoma papilliferum associated with naves sebaceous of jadassohn and squamous cell carcinoma - Sandeep Ojha; Rubal Jain; Abhishek Sharma (Wolters Kluwer Medknow Publications, 2018)
Syringocystadenoma papilliferum (SCAP) is a rare skin adnexal neoplasm of apocrine gland. One-third of SCAP cases are associated with nevus of Jadassohn. Its transition to squamous cell carcinoma is a rare entity. A strong clinical acumen, prompt excision, and confirmation by histopathology underline treatment of this cutaneous tumor. We report a case of this rare association in the deltoid region of a 55-year-old female.